Design Of MRP (Material Requirement Planning) Application Using Data Flow Diagram (DFD) System Approach And Entity Relationship Diagram (ERD) - Siregar, M Tirtana (International research journal of management, IT and social sciences, 2022)
The objective of this research is to design and build an information system for manufacturing processes that fits the requirements of small automotive component industrial enterprises. The waterfall method was used to construct this information system; this method is used to examine the object of research that will be carried out beginning with the background of the organizational structure and other items that may be utilized for the object of research. SWOT analysis is the first stage in analyzing the company’s most pressing information system requirements. Analyze the system design DFD (Data Flow Diagram) is a type of analysis used in business management or inside organizations to systematically assist in the design of the information system to be designed. The ERD (Entity Relationship Diagram) structure approach is required to examine the programming code required to develop a web-based information system. Following the company’s primary requirements, particularly the MRP (Material Requirement Planning (MRP) system), which is included in the scope of activities. Material requirements for orders received are calculated by taking stock levels and reject ratios into account, as well as reports on incoming and outgoing items, Material Requirements, Requirements Production, Data Warehouse, and Delivery / Delivery.